Why IACUCs Need Ethicists. (28th December 2020) - Nobis, Nathan
Abstract: Some animal research is arguably morally wrong, and some animal research is morally bad but could be improved. Who is most likely to be able to identify wrong or bad animal research and advocate for improvements? I argue that philosophical ethicists have the expertise that makes them the likely best candidates for these tasks. I review the skills, knowledge, and perspectives that philosophical ethicists tend to have that makes them ethical experts. I argue that, insofar as Institutional Animal Care and Use Committees are expected to ensure that research is ethical, they must have philosophical ethicists as members.